Energy Resource Assessment Through Hydrodynamic Modeling of Marine Currents in Pulau Pisang Strait, Pesisir Barat, Lampung - Suciana Suciana (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2026)
As an archipelagic nation, Indonesia holds tremendous potential for the development of renewable energy, one of which is ocean current energy, recognized for its stability, cleanliness, and sustainability. Pesisir Barat Regency in Lampung Province is a coastal region rich in marine resources, yet it still faces challenges related to dependence on fossil fuels and limited electricity infrastructure, particularly on Pulau Pisang. Despite being a world-class tourism destination, Pulau Pisang remains off-grid and relies solely on diesel generators. This study aims to address these issues by conducting hydrodynamic modeling using Delft3D software across 11 coastal districts and mapping the potential of Ocean Current Power Plants. The simulation results highlight the Pulau Pisang strait, the strait between Pulau Pisang and the mainland, as the most promising location. This area features mixed semidiurnal tidal characteristics, with average current velocities reaching 0.52 m/s and peak velocities up to 5.40 m/s. Based on the hydrodynamic profile and energy conversion efficiency, the Gorlov turbine is identified as the most suitable technology, with an estimated maximum energy output of 94,647.79 kW. The generated energy is intended to supply Pulau Pisang, supporting its transformation into an energy-independent and sustainable tourism zone, and paving the way for a clean energy-driven local economic transition.